Pembuatan Direktori Lokasi Bermain Skateboarding di Sumatera Barat - Putra, Dian Mega; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractWriting this paper aims to create a directory of locations for skateboarding in West Sumatra. The method used in this paper is descriptive research, which examines a group of people, an object, a condition, a thought, or a class of events in the present. Data collection is done by observation, interview, and literature study. Based on data analysis, it can be concluded as follows. First, the obstacles in making a skateboarding directory location in West Sumatra can be described as follows. (a) the writer has difficulty finding a clear place about the location of skateboarding. These constraints are due to the absence of a clear pointer or direction to a skateboarding location. (b) the distance from the downtown or downtown. These constraints are due to inadequate access to locations. The author must ask and explain to the surrounding community in detail in a location in order to get to the point where to skateboard. (c), the authors find it difficult to find the right sources for more detailed information on a skateboarding location. The existence of these obstacles is due to ignorance of the community and skateboarding community about the place. The author only gets some clear information when making observations. Second, the author's attempt to do so is as follows. (a) the author does his best to make clear road and road directions to a skateboarding location with the help of the surrounding community and the communities in the place. With the help of the community and community in making instructions at a predetermined point or better known by the community. (b) the author tries to minimize the distance to the location of skateboarding by asking the informant or the right informant at a skateboarding location. (c) the author tries his best to do interviews with several people to get clear and precise information about a skateboarding location. The resource person can come from the community itself or the community around the location.Keywords: directory, skateboarding, West Sumatera